Effective Strategy in Writing with WhatsApp in EFL Context - Ketut Andita Rai Savitri (International Journal of English Education and Linguistics (IJoEEL), 2022)
The implementation of 21st century learning in the world help teachers and students interact even remotely with the use of IT, 21st century learning focuses on the use of IT during their learning process IT relates to the use of technology during learning activites, technology is flexible can access it anytime and anywhere. Teachers and students are required to learn how to use IT so the learning activities will run smoothly. IT facilitates learning activities, teachers can send material to students through applications, one of the applications is WhatsApp. Various learning activities can be done on WhatsApp. Nowadays, students’ interests with writing are very low, not all of students interest with writing. By the use of WhatsApp can help to improving students’ writing skill, the teacher should know what students like and give students interesting materials that can increase students’ writing skill, students can explore their knowledge by write the materials on WhatsApp and also students can exchange ideas with other students and also the teachers about the materials. In addition, the use of WhatsApp has advantage, the advantage is teachers and students can do the learning activities with no time limit. The use of WhatsApp can supported by mobile assisted language learning (MALL). This study used descriptive qualitative approach.This study aimed to find out the implementation of WhatsApp application during learning activities. The subject of this study was EFL teacher. The data develop by giving information about the effective strategy in writing using WhatsApp in EFL context.